2003
DOI: 10.1002/crat.200310004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crystallization conditions on the mechanism and rate of crystal growth of potassium sulphate

Abstract: Growth rate of potassium sulfate crystals was studied in a fluidized bed crystallizer. Higher growth rates were observed at larger bed heights. Larger crystals grow faster than smaller size crystals due to the changed fluid dynamics. The growth rate was found to be very sensitive to the pH value of the solution. The growth rate increases with increasing the pH value and the increase of growth in the acidic medium is faster than in the basic medium. The presence of small amounts of Cr 3+ ions reduces the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 11 publications
6
29
0
Order By: Relevance
“…Oslo-Krystal Evaporative Crystallizer ( Figure 2C) [5] The operation is similar to that of APV Kestner or Swenson evaporative crystallizers, where the feed (1) passes through a pump (2) and a heat exchanger (3). The flow enters in an upward direction at position (4) of the crystallizer (5) below the liquid level (6).…”
Section: Swenson Evaporative Crystallizer (mentioning
confidence: 99%
See 3 more Smart Citations
“…Oslo-Krystal Evaporative Crystallizer ( Figure 2C) [5] The operation is similar to that of APV Kestner or Swenson evaporative crystallizers, where the feed (1) passes through a pump (2) and a heat exchanger (3). The flow enters in an upward direction at position (4) of the crystallizer (5) below the liquid level (6).…”
Section: Swenson Evaporative Crystallizer (mentioning
confidence: 99%
“…The Figure 2I-K are examples of stirred tank crystallizers. Figure 2I shows a typical batch adiabatic crystallizer, which consists of a tank (1), propeller (2) and baffles (3). Vacuum (4) is applied at the top facilitating the vaporization of the solvent and results into evaporative cooling of solution.…”
Section: Swenson Evaporative Crystallizer (mentioning
confidence: 99%
See 2 more Smart Citations
“…The solubility and supersolubility enclose the metastable zone, which is a very important parameter for crystallization processes because therein all crystallization processes take place. It was already shown that trivalent metal ions can affect both, solubility [3,8] and supersolubility [6,9] and, therefore, the width of the metastable zone (MZW).…”
Section: Introductionmentioning
confidence: 99%